Programa computacional (PROIRRIGA) para avaliação da uniformidade em irrigação por gotejamento e sua validação - Reisdörfer, Marcelo (2009)
The uniformity in trickle irrigation systems is affected by factors hydraulic, air, lack of maintenance and poor quality of irrigation water resulting in poor distribution of water, either excessive or insufficient, causing loss of productivity. Considering the increased use of automated drip irrigation on farms based on the Family Farm, this work established the objective of preparing the computer program proIRRIGA for Windows in Delphi language with support for three languages (Portuguese, Spanish and English) in order to assist the user in the assessment of uniformity of water in irrigation systems, drip irrigation, using the methodologies KELLER, KARMELI and DENÍCULI. The system suggests to the user based on the data analyzed to fix the total water depth required (ITN), classifying the irrigation system in accordance with the Coefficient of Uniformity of Distribution, Statistical Uniformity Coefficient, Coefficient of Variation of manufacturing, and provide graphs of dispersal and distribution to help the user to find possible defects or system failures. To validate the proIRRIGA implanted with an irrigation system drip where it was found that the methodologies employed (12,16,32,40 drip) submitted to the T test does not differ statistically from one another at the 5% significance level, indicating that are valid for the analysis of uniformity of water application to 14 kPa irrigation systems in small businesses. The overall average presented in accordance with the test is 88.12% for the CUD with a coefficient of variation of 3.86%, showing that for small systems the uniformity of water distribution can be evaluated using the CUD and CUE. The CVf issuers were classified as category B - marginal.